Toward balanced Arab regional investment regulations - Moataz Hussein (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
The post-Arab Spring challenges that affected business climate in the Arab region have prompted many countries to revise their investment policies to balance investors' and states' rights and obligations. Although there has been some success regarding national legal frameworks for FDI, efforts within regional frameworks have not been so effective.
Keywords: 330